Letter from Bessie Cahill to Lily O'Brennan concerning the death of Eileen Ryan - Cahill, Bessie; O'Brennan, Lily M., 1878-1948 (1924)
Cahill writes "She was very fond of you, and I know you will say a little prayer for her after [...] Her death leaves a terrible void in my life, everything is so different".
Keywords: O'Brennan, Lily M., -- 1878-1948 -- Correspondence; Ireland -- History -- 1922-